Growing Interest in Learning Class IXa Students at Smp Negeri 7 Sukabumi Through Optimizing Practicum Learning in The Laboratory - Murni Desi; Hidayati Herlina; Suhendar Suhendar (Equator Science Journal, 2024)
The aim of the research is to foster students' interest in learning in Class IX A of SMP Negeri 7 Sukabumi City through optimizing learning in the laboratory. This experimental research was carried out in class IX A of SMP Negeri 7 Sukabumi City in 2024/2025, consisting of 28 students, 15 male students and 13 female students. This research was carried out for 13 days from August 8-20, 2024. The research results proved that "Optimization of Practical Learning in the Laboratory can be achieved. "Growing Students' Interest in Learning", especially science subjects in class IX A of SMPN 7 Sukabumi City.Before the action, students' interest in learning was still categorized as low, from the results of the initial survey, students' interest in learning only reached 46.4%, with the criteria of 5 indicators of interest in learning, namely feelings of joy, interest, attention, participation, desire/awareness of science learning. After the action, interest in learning science in class IX A reached 64.8%.